Transformation of food systems: How can it be financed? - Díaz-Bonilla, Eugenio (Higher Education Press, 2023)
The paper provides a review of the work on financing the transformation of food systems done by the author and colleagues at IFPRI. The analysis discusses the objectives of that transformation (related to the Sustainable Development Goals and the Paris Agreement) and shows estimates of the costs involved. Then it presents an evaluation of the existing financial flows and their potential scaling up, using a broader view of six main flows involved: two that are internal to food systems (consumer expenditures on food and related items, which are the main source of revenue (as sales) for the variety of actors on the supply side of food systems); and four that are external (international development funds, public budgets, banking systems, and capital markets). The paper notes that although current funding does not reach the scale needed to finance the desired transformation of food systems, there are sufficient potential financial resources available in the aggregate to achieve such transformation. However, to mobilize the existing potential funds the paper discussed several things that need to be done, starting with an adequate macroeconomic and overall incentive framework to guide both the internal flows related to consumption and production decisions, as well as the four external ones. The paper also suggested other possible interventions to mobilize, reorient, and increase the financial flows to the desired objectives. It further noted that the costs and financing, which in the paper were discussed at the global level, must be estimated at the country level, as part of the design and implementation of adequate national plans for equitable, healthy and sustainable food systems.